Evaluation of insecticides to control cotton boll weevil - Ramalho, Francisco S.; Jesus, Fernando M. M. (Pesquisa Agropecuaria Brasileira, 2014)
The work was conducted in the Zangalheira, Farm, Gurinhérn, PB, Brazil, in 1985 canon season, in order to quantity the efficiency of some insecticides to control boll weevil (Anthonomus grandis). The data obtained demonstrated that: 1) Cypermethrin (Nurelle 250 EC), 50 and 62.5 g a.i/ha, Cypermethrin ED (Cymbush 30 ED, white nozzle), 7.81 g a.i/ha and Carbaryl (Carvin 85 WP), 2,0409 a.i/ha, were efficient against cotton ball weevil; 2) Cypermethrin (Nurelle 250 EC), 50 and 62.5 g a.i/ha, Cypermethrin ED (Cymbush 30 ED, white nozzle), 7.81 g a.i/ha and Carbaryl (Carvin 85 WP), 2,0409 a.i/ha, maintained the infestation of cotton squares (oviposition and/or feeding punclures) by colion boli weevil, below lhe economic lhreshold (ET = 101/. ot squares with oviposition and/ar feeding punctures), up to eight days after the last spray, and 3) three sprays of Carbaryl (Carvin 85 WP), 2,040 a.i/ha, at Intervals of four days, decreased the infestation of squares by canon boll weevil to below the economic threshold, in eight days after the last sprays.